Antagonistic Effects of Bacterial Rhizosphere of Oil Palm in Biocontrol of Basal Stem Rot Disease (Ganoderma boninense Pat.) - Widiantini, Fitri; Nugraha, Gema Takbir; Yulia, Endah; Nasahi, Ceppy (HAYATI Journal of Biosciences, 2024)
Basal stem rot disease caused by Ganoderma boninense is a major problem for oil palm cultivation. The research was conducted to obtain biocontrol agents from rhizosphere of oil palm to control the disease as part of sustainable pest management in oil palm plantation. Rhizosphere bacteria were isolated from rhizospheres of healthy oil palm trees. Isolation of bacteria was done using serial dilution method. The isolated bacteria were then tested for its antifungal activity against G. boninense in vitro using dual culture assay. The ability of the bacteria to produce antifungal compound was also determined by culturing the bacteria on ISP2 liquid media. Once the bacterial cells were removed, the crude metabolites were then tested against G. boninense using agar well diffusion and toothpick colonization. The result showed that several isolates demonstrated strong antifungal activity against G. boninense. Some isolates were also able to degrade chitin and to solubilize phosphate. Furthermore, the crude metabolites produced by the rhizosphere bacteria demonstrated the ability to inhibit the growth of G. boninense in the agar diffusion method. Colonization of the G. boninense on toothpick following soaking in the crude metabolites was also inhibited. The isolated rhizosphere bacteria (BARK7 and BARK15 in which identified as Burkholderia sp.) showed promising ability to be developed as biocontrol agent for basal stem rot disease of oil palm.